(3GdLhGgQ GdeLehYI hGdfhGOQ GdeSehYIs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3hHYO aEf ef habg Gddg dQTOg hHdZg fgGjI Cedg hbUOg Cdgeg dRjGQI GdeSGLO GdKdGKI GdeTghQI hcfJ HMeO Gddg JYGdi eef ML hRGQ s
(3BNQgG (B:s
(3bGd cGf GdfHi Udi Gddg Ydjg hSde jOYhG HgPg GdOYhGJ hfNJe HgG bhdg Gddge CUdM PGJ HjffG hGgOfG SHd GdSdGe hCNQLfG ef GdXdeGJ Edi GdfhQ BNQ GdLhGgQ GdeLehYI hGdfhGOQ GdeSehYI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs